Reviewing Economic Growth from The Perspective of Digital Ecosystems and Money Volatility - Ali Farhan; Ayu Rachmawati (PT Maju Malaqbi Makkarana, 2026)
The massive expansion of financial access through digital instruments has stimulated growth in money demand, which in turn drives the volatility of money in circulation. This research aims to examine whether the existence of digital ecosystems and internet access which facilitate easier money usage impacts the economy. Furthermore, it investigates whether the ease of access leading to increased money volatility can moderate the influence of other variables on economic growth. Using a sample of Indonesia's economic conditions from 2023–2024, this research finds that QRIS and Internet Access have a positive and significant effect on economic growth, while money volatility has a negative but insignificant impact.